2015
DOI: 10.1002/ptr.5394
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose-lowering Effect ofT. procumbensL.: A Pilot Clinical Study in Individuals with Type 2 Diabetes

Abstract: Traditional knowledge, in vitro studies, and studies using animal models suggest that Tridax procumbens L. exhibits blood glucose-lowering properties and antiinflammatory effects. In this study, we evaluated the blood glucose-lowering effect of T. procumbens supplementation in individuals with type 2 diabetes. An extract (asava) of T. procumbens L. was prepared following Ayurveda guidelines. Chemical and microbial analyses indicated presence of phenolics, flavonoids, and carotenoids, and absence of microbial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Animal studies showed that extracts of the leaves and of the whole plant have anti-diabetic and anti-hyperlipidaemic activity (Bhagwat et al, 2008;Pareek et al, 2009;Petchi et al, 2013). A pilot 4-week clinical study revealed that when administered to individuals with type 2 diabetes, an extract of the whole plant of T. procumbens (containing carotenoids, flavonoids and other phenolics) lowered blood glucose with no serious adverse effects reported (Desai et al, 2015). We also found a report of its use to treat kidney disease in El Salvador (Gonzalez-Ayala, 1994).…”
Section: Plant Species Used To Treat Diabetes and Its Sequelae In Cenmentioning
confidence: 99%
“…Animal studies showed that extracts of the leaves and of the whole plant have anti-diabetic and anti-hyperlipidaemic activity (Bhagwat et al, 2008;Pareek et al, 2009;Petchi et al, 2013). A pilot 4-week clinical study revealed that when administered to individuals with type 2 diabetes, an extract of the whole plant of T. procumbens (containing carotenoids, flavonoids and other phenolics) lowered blood glucose with no serious adverse effects reported (Desai et al, 2015). We also found a report of its use to treat kidney disease in El Salvador (Gonzalez-Ayala, 1994).…”
Section: Plant Species Used To Treat Diabetes and Its Sequelae In Cenmentioning
confidence: 99%
“…Hence, systematic and intensive search in medicinal plants for new drugs to treat Type 2 diabetes mellitus seem to be of great utility. Plants have been the major source of drugs in Indian system of medicine and other ancient systems in the world (2,3). The present study aims to study the comparative efficacy of hydroalcoholic, aqueous and petroleum ether extracts of Tridax procumbens (Compositae) as antioxidants for the utilization in the treatment of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[ A study carried out by Desai et al 40 was aimed at evaluating the lowering effects on blood glucose concentration resulting from the administration of Tridax procumbens in patients with Type 2 diabetes. The extracts contained phenolics, flavonoids, and carotenoids, according to a chemical examination.…”
Section: Antidiabetic Propertiesmentioning
confidence: 99%